2022
DOI: 10.1038/s41467-022-31168-9
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in endocannabinoid synthase DAGLB contributes to early onset Parkinsonism and murine nigral dopaminergic neuron dysfunction

Abstract: Endocannabinoid (eCB), 2-arachidonoyl-glycerol (2-AG), the most abundant eCB in the brain, regulates diverse neural functions. Here we linked multiple homozygous loss-of-function mutations in 2-AG synthase diacylglycerol lipase β (DAGLB) to an early onset autosomal recessive Parkinsonism. DAGLB is the main 2-AG synthase in human and mouse substantia nigra (SN) dopaminergic neurons (DANs). In mice, the SN 2-AG levels were markedly correlated with motor performance during locomotor skill acquisition. Genetic kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Although pathogenic mutations in disease-causing genes play essential roles in PD, few patients carry pathogenic mutations 5,6 . Common variants with small effect size can be detected via genome-wide association studies (GWASs), and have been shown to affect a large proportion of genetic predisposition of PD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although pathogenic mutations in disease-causing genes play essential roles in PD, few patients carry pathogenic mutations 5,6 . Common variants with small effect size can be detected via genome-wide association studies (GWASs), and have been shown to affect a large proportion of genetic predisposition of PD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Stereotaxic surgery was performed as described previously [4]. The location for SN injection was determined according to the distance from bregma: anterior–posterior = −3.1 mm, medial–lateral = ±1.5 mm, dorsal–ventral = −3.9 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Christelle Tesson, PhD, 1 Mohamed Sofiane Bouchetara, MD, 2 Mélanie Ferrien, MSc, 1 Suzanne Lesage, PhD, 1 and Alexis Brice, MD…”
Section: Ethical Compliance Statementmentioning
confidence: 99%